Answering Orientation Questions and Following Single-Step Verbal Commands: Effect on Aspiration Status - Leder, Steven B.; Suiter, Debra M.; Lisitano Warner, Heather (Dysphagia, 2009)
In the acute-care setting patients with altered mental status as a result of such diverse etiologies as stroke, traumatic brain injury, degenerative neurologic impairments, dementia, or alcohol/drug abuse are routinely referred for dysphagia testing. A protocol for dysphagia testing was developed that began with verbal stimuli to determine patient orientation status and ability to follow single-step verbal commands. Although unknown, it would be beneficial to ascertain if this information on mental status was predictive of aspiration risk. The purpose of this investigation was to determine if there was a difference in odds for aspiration based upon correctly answering specific orientation questions, i.e., 1. What is your name? 2. Where are you right now? and 3. What year is it?, and following specific single-step verbal commands, i.e., 1. Open your mouth. 2. Stick out your tongue. and 3. Smile. In a consecutive retrospective manner data from 4070 referred patients accrued between 1 December 1999 and 1 January 2007 were analyzed. The odds of liquid aspiration were 31% greater for patients not oriented to person, place, and time (odds ratio [OR] = 1.305, 95% CI = 1.134–1.501). The odds of liquid aspiration (OR = 1.566, 95% CI = 1.307–1.876), puree aspiration (OR = 1.484, 95% CI = 1.202–1.831), and being deemed unsafe for any oral intake (OR = 1.688, 95% CI = 1.387–2.054) were, respectively, 57, 48, and 69% greater for patients unable to follow single-step verbal commands. Being able to answer orientation questions and follow single-step verbal commands provides information on odds of aspiration for liquid and puree food consistencies as well as overall eating status prior todysphagia testing. Knowledge of potential increased odds of aspiration allows for individualization of dysphagia testing thereby optimizing swallowing success.
Keywords: Aspiration; Cognition; Deglutition; Deglutition disorders; peer-reviewed

Fiberoptic Endoscopic Evaluation of Swallowing (FEES) with and without Blue-Dyed Food - Leder, Steven B.; Acton, Lynn M.; Lisitano, Heather L.; Murray, Joseph T. (Dysphagia, 2005)
The purpose of this prospective study was to determine if fiberoptic endoscopic evaluation of swallowing (FEES) maintains high intra- and interrater reliability in detecting pharyngeal dysphagia and aspiration without the addition of FD&C Blue No. 1 to food. Twenty consecutive adults referred for a swallow evaluation participated. Nine subjects received blue-dyed food and 11 subjects received regular nondyed food, i.e., yellow pudding and white skim milk. Four variables were rated: (1) the stage transition characterized by depth of bolus flow to at least the vallecula prior to the pharyngeal swallow; (2) evidence of bolus retention in the vallecula or pyriform sinuses after the pharyngeal swallow; (3) laryngeal penetration defined as material in the laryngeal vestibule but not passing below the level of the true vocal folds either before or after the pharyngeal swallow; and (4) tracheal aspiration defined as material below the level of the true vocal folds either before or after the pharyngeal swallow. Three speech–language pathologists experienced in interpreting FEES results independently and blindly reviewed the digitized videotape three times. Intrarater agreements for the four variables with blue-dyed and non-blue-dyed food trials were 100% and monochrome trials ranged from 95% to 100%. Average kappa values for interrater reliability ranged from moderate to excellent agreement (0.61–1.00) for all viewing conditions. Kappa values for blue-dyed trials versus monochrome trials were 0.83 and for non-blue-dyed trials versus monochrome trials were 0.88, indicative of excellent reliability under both viewing conditions. FEES maintains both high intra- and interrater reliability in detecting the critical features of pharyngeal dysphagia and aspiration using either blue-dyed or non-blue-dyed foods. The endoscopist, therefore, can be assured of reliable FEES results using regular, non-dyed food trials.
Keywords: Aspiration; Blue dye; Deglutition; Deglutition disorders; Fiberoptic endoscopic evaluation of swallowing; Pharyngeal dysphagia; dept.cmd; peer-reviewed